THE EFFECT OF LEVERAGE, INSTITUTIONAL OWNERSHIP, AND PROFITABILITY ON TAX AVOIDANCE WITH COMPANY SIZE AS A MODERATING VARIABLE IN HEALTHCARE SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FOR THE 2021 – 2023 PERIOD - Dewi Rahmahwati; Sifa Widiyana; Shafira Cahyani Wulandari; Mohamad Zulman Hakim; Seleman Hardi Yahawi; Wati Yaramah (ZILLZELL MEDIA PRIMA, 2025)
This study intends to understand the impact of Leverage, Institutional Ownership and Profitability on Tax Avoidance through Company Size as a moderation variable. The population of this study is Healthcare Companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The population is 33 companies using the purposive sampling method with 15 companies that meet the requirements, with a large amount of observation data of 45 data. This data study uses the method of combined data regression analysis through the E-views 12.0 program. The findings of the study prove that Leverage and Profitability have a negative impact on Tax avoidance. Institutional ownership has a positive impact on tax avoidance. Company Size can moderate the impact of Leverage, Institutional Ownership and Profitability on Tax avoidance.